Development Problem-BasedLearning Oriented E-worksheet To Train Analytical Skills On Chemical Equilibrium Material - Damayanti, Vivi; Novita, Dian (Universitas Pendidikan Mandalika, 2024)
The purpose of this study is to discuss the possibility of using a problem-based learning-oriented e-worksheet to teach students analytical skills on chemical equilibrium material. The feasibility of E-LKPD may be assessed in terms of validity, practicality, and efficacy. The approach employed in this study is Research and Development (R&D), utilizing the 4D development process derived by Tiagharajan, which covers Define, Design, Develop, and Disseminate. Based on the findings of the research, the e-worksheet earned mode 3 on the validation sheet, indicating that it is legitimate. The e-worksheet was deemed extremely practical based on the findings of the student response questionnaire, with a percentage of 86.44%. The e-worksheet is certified effective in terms of analyzing t test findings with a significance value of 0.00, implying that Ho is rejected and Ha is accepted. The n-gain score for analytical skills was 0.55 on element analysis, 0.59 on relationship analysis, and 0.59 on organizing analysis. Based on these findings, it is possible to infer that the problem-based learning-oriented e-worksheet produced to educate students' analytical abilities on chemical equilibrium content is suitable for usage.Â